PEMENUHAN NUTRISI PADA IBU HAMIL DI POLI KEBIDANAN RS CIPUTRA HOSPITAL 2021 - Ratnasari, Febi; Kunayah, Kunayah; Indahwati, Sri; Fatmala, Tika; Sundari, Uci (Nusantara Hasana Berdikari, 2022)
During pregnancy, nutrition is the most important influence for fetal growth and development. If pregnant women have problems with nutritional intake, it will greatly affect the fetus. If the nutrition is balanced and sufficient, the fetus will be healthy both in the womb and at birth, if the nutrition is not balanced and adequate, the fetus will have a bad impact, resulting in possible abnormalities in the fetus. Research objectives to provide knowledge to pregnant women about good nutrition for fetal development during pregnancy. This study was conducted directly or face to face with 1 participant who was a pregnant patient of the obstetrics polyclinic ofÂ Ciputra Hospital. After being given health education on the fulfillment of nutrition for pregnant women, it was found that the participants understood the importance of fulfilling good nutrition for pregnant women. Nutrition of pregnant women is very important for the mother and fetus so that fetal development does not occur abnormalities.